2021
DOI: 10.3390/ijerph18179059
|View full text |Cite
|
Sign up to set email alerts
|

How Mentally Fatiguing Are Consecutive World Padel Tour Matches?

Abstract: It is currently unknown whether mental fatigue occurs throughout a WPT competition and whether consecutive matches affect how mentally fatiguing a match is perceived to be. The objective was to quantify the effects of successive professional matches on mental fatigue. A total of 14 professional players (9 males, Mage = 25, 5 females, Mage = 21) participated during qualified rounds of a WPT with three eliminatory matches: Match 1 (morning) and 2 (afternoon) on day 1 (n = 14), Match 3 (morning) on day 2 (n = 6).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
(44 reference statements)
1
24
1
Order By: Relevance
“…A total of 479 padel players with a different level of experience were included in the studies and 1098 matches were also analyzed. Most of the studies are cross-sectional ( n = 3) [ 7 , 10 , 15 ] and observational ( n = 12) [ 3 , 7 , 9 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]; studies on match analysis utilized the systematic observation of padel match videos from official channels. The current literature argues over four different aspects of padel: match analysis, anthropometric and physical fitness, the biological effects of padel matches on athletes, and the risk of injury and rehabilitative approaches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 479 padel players with a different level of experience were included in the studies and 1098 matches were also analyzed. Most of the studies are cross-sectional ( n = 3) [ 7 , 10 , 15 ] and observational ( n = 12) [ 3 , 7 , 9 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]; studies on match analysis utilized the systematic observation of padel match videos from official channels. The current literature argues over four different aspects of padel: match analysis, anthropometric and physical fitness, the biological effects of padel matches on athletes, and the risk of injury and rehabilitative approaches.…”
Section: Resultsmentioning
confidence: 99%
“…The current literature argues over four different aspects of padel: match analysis, anthropometric and physical fitness, the biological effects of padel matches on athletes, and the risk of injury and rehabilitative approaches. Almost all the study included were from Spain ( n = 16) [ 3 , 7 , 9 , 10 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]; only one was from Sweden [ 26 ]. Ten of the included studies investigated game dynamics [ 3 , 9 , 12 , 16 , 17 , 18 , 19 , 20 , 21 ], of which one [ 12 ] analyzed the court zone involved in the attacking and defensive phase of the match; six studies [ 3 , 16 , 17 , 19 , 20 , 21 ] investigated padel strokes, highlighting that the smash is one of the most effective strokes with which to stop the rally; on the other hand, the lob is the most valid in a defensive position [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Díaz-García et al [ 45 ] observed an increase in mental fatigue from pre- to post-world padel tour matches ( p < 0.01) and an impairment in reaction time ( p < 0.04).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from that, some authors reported physical performance tests involving strength, power, and the ability to repeat sprints [ 8 , 42 , 58 , 65 , 67 , 87 ], serving as a reference for those athletes aiming to improve their performance. Another interesting—and less researched—issue was mental performance, with only one report focused on it, suggesting that inter-game mental fatigue could impair reaction times [ 45 ].…”
Section: Discussionmentioning
confidence: 99%